Strategy of Management of The Supply Money (UP) and The Additional Supply Money (TUP) within the National Resilience Council - Pamungkas, Andre; Rayahu, Neneng Sri; Karunia, R. Luki (International Journal of Economics Development Research (IJEDR), 2024)
The purpose of this study is to identify and analyze the causes of not optimal yet of management of The Supply Money (UP) and The Additional Supply Money (TUP) within the National Resilience Council and to develop strategies so that the management of UP and TUP within the National Resilience Council to be optimal. This research uses a case study research method with a qualitative approach. The results showed that in 2022, the management of UP and TUP within the National Resilience Council has not been optimal. Despite having a clear legal basis and appropriate procedures, as well as a competent treasurer, there are still obstacles such as lates in TUP accountability, a low percentage of UP's change, and TUP deposits. This is partly due to the absence of specific internal policies to manage UP and TUP according to the conditions of the National Resilience Council. In addition, although cashless payment facilities are already available, the National Resilience Council has not optimized them, even though this can reduce the risk of lates and fraud. The government's commitment in giving appreciation to work units that run the budget well also supports this effort. When it comes to cash flow forecasting management, the role of leader in information system is crucial, but the problem of lack of awareness of each units to calculate committedly and consistently hinder the accuracy of forecasting. In addition, an effective forecasting model has not been implemented and internal supervision focuses more on operational audits than the management of UP and TUP, which are only evaluated during coordination meetings and preparation of financial statements at the end of the period. Based on the results of research with the analysis of Strengths, Weaknesses, Opportunities, and Threats (SWOT), is obtained in quadrant 3 (three) which can be interpreted that the National Resilience Council has weaknesses but very opportunities. This condition can also be interpreted as a situation where faced with great opportunities but there are weaknesses. The focus of the strategy that can be implemented on these conditions is to change the previous strategy so that it is expected to minimize problems and implement better opportunities.